Impact of E-Service Quality Dimensions on Customer Satisfaction and Loyalty in Online Apparel Shopping in India - Mahadevan, Kala; Joshi, Sujata (Indian Journal of Marketing, 2022)
This study aimed to assess the impact of the e-service quality dimensions on customer satisfaction and loyalty in the online apparel market in India. The study examined the direct effect of e-service quality dimensions on customer satisfaction and the effect of customer satisfaction as a mediator in the relationship between the e-service quality dimensions of fulfillment, privacy, efficiency, system availability, and customer loyalty. The study used a descriptive design and collected data from 239 respondents in 2020. Data were analyzed using statistical tools such as Statistical Package for Social Sciences (SPSS) and analysis of moment structures (AMOS). A confirmatory factor analysis was carried out to assess model fit, and path analysis using AMOS was used to test the direct relationships. The mediation effect of customer satisfaction between the dimensions of e-service quality with customer loyalty was tested through the PROCESS Macro package. While the e-service quality dimensions of fulfillment and privacy positively influenced customer satisfaction, efficiency and system availability did not lead to customer satisfaction. However, customer satisfaction partially mediated all four dimensions of e-service quality and customer loyalty. This study contributed to the academic literature by testing the E-SERVQUAL model in India’s online apparel shopping context. The study was relevant to online apparel retailers by identifying fulfillment and privacy as key dimensions influencing customer satisfaction amongst online apparel customers in India.